Handbook of research on software-defined and cognitive radio technologies for dynamic spectrum management - Kaabouch, Naima, 1959-; Hu, Wen Chen, 1960-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book examines the emerging technologies being used to overcome radio spectrum scarcity, providing timely and comprehensive coverage on topics pertaining to channel estimation, spectrum sensing, communication security, frequency hopping, and smart antennas"--Provided by publisher.
Radio spectrum sensing -- Radio spectrum management and access -- Software-defined radio and antennas for cognitive radio networks -- Models, security, and other related topics.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 02/25/2015).
Keywords: Cognitive radio networks; Radio frequency allocation -- Management; Channel allocation; Channel reservation; Microelectromechanical systems; Modulations techniques; Predictive models; Electronic books